Population pharmacokinetic and exposure‐response analyses of ivosidenib in patients with IDH1‐mutant advanced hematologic malignancies. Issue 3 (25th January 2021) - Jiang, Xuemin; Wada, Russ; Poland, Bill; Kleijn, Huub Jan; Fan, Bin; Liu, Guowen; Liu, Hua; Kapsalis, Stephanie; Yang, Hua; Le, Kha
Abstract: Ivosidenib is a once daily (q.d.), orally available, potent mutant isocitrate dehydrogenase 1 (mIDH1) inhibitor approved for treatment of patients with relapsed or refractory (R/R) acute myeloid leukemia (AML) and intensive chemotherapy ineligible AML with a susceptible IDH1 mutation. Population pharmacokinetics (PKs; N  = 253), exposure‐response (efficacy [ n  = 201] and safety [ n  = 253]), and concentration‐corrected electrocardiogram QT interval (QTc; n  = 171) analyses were performed using phase I data (100 mg twice daily and 300–1200 mg q.d.). Ivosidenib disposition was well‐described by a two‐compartment PK model with first‐order absorption and elimination. Between‐subject variability was moderate for PK parameters. Intrinsic factors did not affect ivosidenib PKs. Moderate/strong CYP3A4 inhibitors increased the area under the plasma ivosidenib concentration‐time curve at steady state (AUCss ) by 60%. Efficacy responders and nonresponders had similar ivosidenib exposures. Based on AUCss, there was no apparent relationship between ivosidenib exposure and efficacy or adverse events. The plasma ivosidenib concentration‐QT analysis showed a mean change in QTc using Fridericia's method (ΔQTcF) of 17.2 msec at the approved 500 mg q.d. dose. Because of the direct association between ivosidenib exposure and QTcF, patients should have their electrocardiograms and electrolytes monitored, and comedications that increase ivosidenib exposure or prolong the QT interval should be avoided. These model‐based analyses quantitatively provide a framework to describe the relationship among ivosidenib dose, exposure, and clinical end points. With precautions for QTc prolongation, the exposure‐response analyses support the 500 mg q.d. dose in patients with AML with a susceptible IDH1 mutation.